Auditing Corporate Reports and Financial Statements Externally: Truth or Mirage (International Journal of Financial, Administrative and Economic Sciences, 2024)
The separation of ownership and management in the corporate model resulted in the need for an external party to certify the representation of the financial statements prepared by the corporation’s executive management of its financial position and the financial, cash and operational performance of its executive management. The existence of the corporation whose shares are traded in the market and stock exchanges also resulted in the emergence of a class in society, lurking for price fluctuation. Accounting has founded a concept that it is the servant of every rational decision maker. However, the concept of 'decision makers' in accounting is imaginary. Financial accounting has not been able for more than a century and until our present moment to provide a model for the financial statements and reports that the corporation is required to prepare and publish in response to their so-called needs of its financiers. The financial statements are prepared based on financial accounting standards, which represent the contemporary accounting truth. Such truth is impossible and is not a reflection of the economic reality on which the accounting entity is constructed.The external auditor’s approval of the corporate financial statements prepared by its executive management makes him its partner in preparing the financial statements and reports. What gives value to the opinion of the external party is his possession of the technical knowledge that gives him an advantage over the rest of the members of his society, and his independence from the executive management is the foundation of his work and professionalism. However, academic research in accounting and auditing casts doubt on the objectivity of the external auditor and even his ability to be independent, as their relationship is closer to cooperation than to opposition, representing the interests of the party absent from the contractual relationship between them. External auditing is the only profession whose practitioner must monitor whom he receives his fees in service to watch the interest a part that is absent in the contractual relationship. The external auditor does not provide the service of auditing the financial statements and reports of corporations as a community or voluntary service, but rather it is a service in exchange for covering his expenses and achieving a source of income. Also, work skills and dealing with the audit firm’s clients are of great importance in the audit firm, and leadership. Reliance on the one-partner model in implementing audit engagements is a source of risk. The external auditor is a product of his society. The doctrine that his society follows is his belief, and it is what affects his decisions. It is the balance of matters. Strengthening the independence of the external auditor, even in the presence of legislation, is not sufficient for the independence of the mind of the external auditor.
Keywords: Corporate Accounting; Auditing; Truth